Resilience Strategies Among Non-Working Wives In Dealing With Marital Problem (Phenomenon Of Couples Early Phase Under 3 Years Of Marriage) - Sarasih, Pin Gunita; Harahap, Dewi Handayani; Rahma, Izzah Annisatur (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Marriage is one of the stages in adult life that bring major change, both emotionally and socially. Marriage under three years is considered an early phase, where couples are still adapting and getting to know each other's characters. This phase is often considered a period of adaptation and adjustment of communication, economy, and adaptation to the extended family for married couples. This study aims to understand the resilience strategies applied to non-working wives in dealing with marital problems in the early phase of marriage less than three years. The study used a descriptive qualitative approach that allows researchers to understand the picture of the dynamics of the subject. The results of the most widely used resilience research by non-working wives are that emotional regulation and positive self-acceptance play a very important role in maintaining the harmony of a marriage relationship. The presence of factors that emerge such as cultural dynamics, the presence of children and communication are interconnected and make a major contribution to creating relationship that is mutually supportive and full of understanding. The implications of this study indicate that the development of resilience strategies is very important for non-working wives in managing conflict and maintaining marital harmony, especially in the early phase of marriage. Pernikahan merupakan salah satu tahapan dalam kehidupan dewasa yang membawa perubahan besar, baik secara emosional maupun sosial. Pernikahan di bawah tiga tahun dianggap sebagai fase awal, di mana pasangan masih beradaptasi dan saling mengenal karakter masing-masing. Fase ini sering dianggap sebagai masa adaptasi dan penyesuaian komunikasi, pengendalian emosi, dan adaptasi dengan keluarga besar bagi pasangan suami-istri. Penelitian ini bertujuan untuk memahami strategi resiliensi yang diterapkan oleh istri yang tidak bekerja dalam menghadapi problematika pernikahan pada fase awal pernikahan kurang dari tiga tahun. Penelitian menggunakan pendekatan kualitatif deskriptif yang memungkinkan peneliti memahami gambaran dinamika subjek. Hasil dari penelitian resiliensi yang paling bayak digunakan oleh istri yang tidak bekerja adalah regulasi emosi dan penerimaan diri yang positif menjadi peranan yang sangat penting dalam menjaga keharmonisan sebuah hubungan pernikahan. Adanya faktor yang muncul seperti dinamika budaya, kehadiran anak dan komunikasi ini saling berhubungan dan memberikan kontribusi besar dalam menciptakan hubungan yang saling mendukung dan penuh pengertian. Implikasi penelitian ini menunjukkan pengembangan strategi resiliensi sangat penting bagi istri yang tidak bekerja dalam mengelola konflik dan menjaga keharmonisan pernikahan, terutama pada fase awal pernikahan.